2017
DOI: 10.1002/ep.12540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and aging on the adsorption and desorption of menadione in soil

Abstract: In this study, the effect of soil temperature and aging on the adsorption and desorption of menadione was investigated using the batch equilibrium method. The obtained isotherm data can be well fitted to the linearized form of the Freundlich equation, with R2 values ranging between 0.91 and 1.00. The adsorption and desorption of menadione in non‐aged (control) soil increased significantly when the temperature ranged between 15 and 37°C. Among soils that were amended with menadione and aged for 72 h, the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The four‐zone effects were observed from contour surfaces, which implies that different responses were obtained for DCF adsorption by the soil M at different DCF concentration and temperature values. This may be due to the interaction between the molecular structure of DCF and ionic structures in the soil M. Therefore, the adsorption of DCF in soil M is likely to be endothermic, which agrees with the finding of Jenkins et al 51 and Gao et al 25 for atrazine, imazapyr, and menadione in soil, respectively. In addition, in endothermic adsorption, an increase in temperature causes a decrease in solution viscosity.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The four‐zone effects were observed from contour surfaces, which implies that different responses were obtained for DCF adsorption by the soil M at different DCF concentration and temperature values. This may be due to the interaction between the molecular structure of DCF and ionic structures in the soil M. Therefore, the adsorption of DCF in soil M is likely to be endothermic, which agrees with the finding of Jenkins et al 51 and Gao et al 25 for atrazine, imazapyr, and menadione in soil, respectively. In addition, in endothermic adsorption, an increase in temperature causes a decrease in solution viscosity.…”
Section: Resultssupporting
confidence: 89%
“…The XRF analysis results of the soils S and M are shown in Table S2 (in Data S1). According to Table S2, Ca dominates the soil S while Si dominates the soil M. These analysis results indicated that quartz for soil M and calcite for soil S as predominant phases 25 . Ca is the dominant cation in the exchange mechanism.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations